The Effect Of Areca Nut (Areca catechu L.) Ethanol Extract On The Morphology and Histology Of Alloxan Induced Rat (Rattus norvegicus L.) Testis - Hutahaean, Salomo; Tambunan, Christoper Arata (Talenta Publisher, 2025)
Some people traditionally use the areca (Areca catechu) nut in Indonesia to cure diabetes; however, information regarding the safety of the areca nut, especially for the reproductive system, still needs to be studied. This study aimed to analyze the effect of administering areca nut ethanol extract on the morphology and histology of testes in alloxan-induced diabetic rats. Twenty-four diabetic rats were divided into six treatments: normal control, alloxan control, 3 treatments of areca nut ethanol extract (100, 200, or 300 mg/kg BW), and metformin 45 mg/kg BW. The treatment was given for 25 days, and on the 26th day, the rats were dissected, and histological preparations were made using the paraffin method and stained with Hematoxylin and Eosin (HE). The results showed that administration of areca nut ethanol extract up to a dose of 300 mg/kg BW was safe for the testis organs and could even increase testis weight, seminiferous tubule diameter, seminiferous tubule germinal epithelial thickness, number of Leydig cells, number of Sertoli cells, number of spermatogonium cells, spermatocytes, spermatids, and spermatogenesis index significantly (p<0.05).